PEMANFAATAN PERMAINAN TRADISIONAL DALAM MENGEMBANGKAN KEMAMPUAN NUMERIK ANAK USIA 5-6 TAHUN DI RA DAARUL MUQIMIEN - Huliyah, Muhiyatul; Yuli Rahmawati; Asep Supena (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
Early childhood numerical skills are a significant factor in academic readiness. A traditional game-based approach is an effective strategy for engagingly enhancing numerical skills. This study explores using traditional games to support the numerical development of 5-6-year-old children at RA Daarul Muqimien. A qualitative and case study approach was employed to collect data through interviews, observations, and documentation. The participants of this study consisted of three teachers, three parents and three children. Data analysis was conducted using thematic analysis techniques to identify emerging patterns. The results showed that traditional games such as Snakes and Ladders, Congklak, and Engklek were used to improve number recognition, addition, subtraction, and forward and backward counting. In addition, these games contribute positively to children’s cognitive, social and motor development. Teachers play a role in adapting the games, while parents support them through guidance at home. The game promotes social interaction and cooperation among children. While there are challenges, such as limited focus and mentoring time, this approach facilitates an engaging learning experience. This research contributes to developing traditional game-based numerical learning methods with adaptations that address children’s needs.